Comparative evaluation of the effect of different resin luting agents on the color of lithium disilicate crowns after Aging (An In Vitro Study) - Lana Bahram Khadhr; Randa Saad Rasheed (Journal of University Medical & Dental College, 2025)
BACKGROUND AND OBJECTIVE: Ceramics made of lithium disilicate are popular because of their superior optical properties and biocompatibility. The aim of this study was to evaluate the cement types that yield the best results and to assess the effects of various resin cements on the shade of lithium disilicate restorations, both before and after thermocycling.METHODOLOGY: Lithium disilicate blocks were used to restore thirty prepared central incisors from typodont teeth. The restorations were cemented with 3 types of resin cement (G-Cem One, Breeze, and Itena).  A spectrophotometer was used to measure the color parameters of the restorations in three stages: 1) prior to cementing, 2) following cementing, and 3) following 5000 cycles of thermocycling. The CIEDE2000 formula was used to calculate color differences (∆E00).  RESULTS: There was no noticeable difference found between the three research groups in the means of ∆E00 1 and ∆E00 2. However, the highest mean was observed in the GC Resin Cement. ∆E00 3 assesses the color change after thermocycling compared with readings after cementing. The means of ∆E00 3 did not differ significantly across the three groups, but Itena Resin Cement has the highest mean.CONCLUSIONS: There was some color change in resin cements of the same color made by different manufacturers, although these changes were usually within clinically normal limits.